Tolerance of soybean genotypes to aluminum in solution - Menosso, Orival Gastão; Costa, José Antonio; Anghinoni, Ibanor; Bohnen, Humberto (Pesquisa Agropecuaria Brasileira, 2000)
The knowledge of the soybean (Glycine max L.) genotypes reaction to aluminum (Al) present in acid soils is important for the development of efficient breeding programs. A series of experiments were carried out to determine the levels of Al and calcium (Ca) in low salt solutions and the most appropriate time for screening. The next experiments were conducted to rank Brazilian soybean cultivars and breeding lines according to their tolerance to Al with some American cultivars, considered as standards. A solution with 0.2 mg L-1 of Al and 50 mg L-1 of Ca was used and the primary root length obtained in the ninth day was utilized to screen 148 soybean genotypes for Al tolerance. Among these genotypes, 21 were Al-tolerant : Biloxi, Bragg, BRAS85-1736, BRAS86-3672, BR-13 (Maravilha), BR-37, Cobb, EMGOPA-302, EMGOPA-304 (Campeira), FT-1, FT-5 (Formosa), FT-6 (Veneza), FT-Guaíra, FT-Manacá, IAS 4, IPAGRO-21, Ivaí, MSBR-17 (São Gabriel), OCEPAR-6, Planalto and Tiaraju. Seventy three genotypes had intermediate tolerance and 54 were non-tolerant to Al.